2013
DOI: 10.1038/cdd.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Dock3 attenuates neural cell death due to NMDA neurotoxicity and oxidative stress in a mouse model of normal tension glaucoma

Abstract: Dedicator of cytokinesis 3 (Dock3), a new member of the guanine nucleotide exchange factors for the small GTPase Rac1, promotes axon regeneration following optic nerve injury. In the present study, we found that Dock3 directly binds to the intracellular C-terminus domain of NR2B, an N-methyl-D-aspartate (NMDA) receptor subunit. In transgenic mice overexpressing Dock3 (Dock3 Tg), NR2B expression in the retina was significantly decreased and NMDA-induced retinal degeneration was ameliorated. In addition, overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 57 publications
1
66
1
Order By: Relevance
“…11,31,44 In addition, overexpression of Dock3 suppressed retinal degeneration in GLAST KO mice. 11 Interestingly, Dock3 signaling is enhanced by brain-derived neurotrophic factor (BDNF), which induces neuroprotection, axonal outgrowth and neurogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…11,31,44 In addition, overexpression of Dock3 suppressed retinal degeneration in GLAST KO mice. 11 Interestingly, Dock3 signaling is enhanced by brain-derived neurotrophic factor (BDNF), which induces neuroprotection, axonal outgrowth and neurogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…11,31,44 In addition, overexpression of Dock3 suppressed retinal degeneration in GLAST KO mice. 11 Interestingly, Dock3 signaling is enhanced by brain-derived neurotrophic factor (BDNF), which induces neuroprotection, axonal outgrowth and neurogenesis. 31,[45][46][47] A recent study has shown that a novel phosphine-borane complex promotes RGC protection through the induction of BDNF and activation of the extracellular signal-regulated kinases (ERK) 1/2.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DOCK3 has been shown to be an essential regulator of cell movement and apoptosis via the modulation of RAC1 signaling by converting RAC1-GDP into RAC1-GTP via DOCK3's GTPase activity (66,76). Normal cellular migration and viability are significantly affected if DOCK3 is overexpressed or silenced, depending on the cell type (62,64).…”
Section: Dock3 Is An Essential Regulator Of Pten/akt and Rac1 Signalimentioning
confidence: 99%
“…[4][5][6] Also, inhibitors of glutamate receptors, tumor necrosis factor receptors, and nitric oxide synthase may be effective for RGC protection. [7][8][9][10][11] The ONI model mimics some aspects of glaucoma, including RGC death induced by oxidative stress, and therefore, it is also a useful animal model for glaucoma.…”
mentioning
confidence: 99%